Bioanalytical method development and validation of levalbuterol a β2-adrenergic agonist by RP-HPLC method - Ghemud, A. S.; Santhakumari, B.; Pharne, A. B.; Jadhav, M. M.; Jain, K. S.; Kulkarni, Mahesh J. (International Journal of Pharmacy and Pharmaceutical Sciences, 2012)

Bioanalytical method development and validation of vildagliptin a novel dipeptidyl peptidase IV inhibitor by RP-HPLC method - Pharne, A. B.; Santhakumari, B.; Ghemud, A. S.; Jain, H. K.; Kulkarni, Mahesh J. (International Journal of Pharmacy and Pharmaceutical Sciences, 2012)
A simple, selective, rapid, precise and economical Reverse-Phase HPLC method has been developed and validated for quantitative determination of vildagliptin in plasma. Vildagliptin is a potent dipeptidyl peptidase IV inhibitor used for treatment of diabetes. Tolbutamide is used as an internal standard. The method was carried out with UV Spectrophotometric detection using a Perkin Elmer Series 200 HPLC system equipped with XBridge Shield C18 column (3.5 μm, 4.6x150mm) and a guard column of the same type, at a flow rate of 1.0mL/min. Detection was carried out at 210 nm. The mobile phase consisted of 50mM ammonium bicarbonate (pH 7.8) (solvent A) and acetonitrile (solvent B). The retention times of vildagliptin and tolbutamide were 11.2 min and 13.4 min respectively. The method was developed and tested for linearity range of 10μg/ml to 120μg/ml. The developed method was validated in terms of selectivity, accuracy, precision, linearity, and stability study. The proposed method uses less biological material and the method is MS compatible also. Method can be applicable for pharmacokinetic studies using HPLC or LC-MS.

Biosurfactant as a promoter of methane hydrate formation: thermodynamic and kinetic studies - Arora, Amit; Cameotra, Swaranjit Singh; Kumar, Rajnish; Balomajumder, Chandrajit; Singh, Anil Kumar; Santhakumari, B.; Kumar, Pushpendra; Laik, Sukumar (Scientific Reports, 2016)
Natural gas hydrates (NGHs) are solid non-stoichiometric compounds often regarded as a next generation energy source. Successful commercialization of NGH is curtailed by lack of efficient and safe technology for generation, dissociation, storage and transportation. The present work studied the influence of environment compatible biosurfactant on gas hydrate formation. Biosurfactant was produced by Pseudomonas aeruginosa strain A11 and was characterized as rhamnolipids. Purified rhamnolipids reduced the surface tension of water from 72 mN/m to 36 mN/m with Critical Micelle Concentration (CMC) of 70 mg/l. Use of 1000 ppm rhamnolipids solution in C type silica gel bed system increased methane hydrate formation rate by 42.97% and reduced the induction time of hydrate formation by 22.63% as compared to water saturated C type silica gel. Presence of rhamnolipids also shifted methane hydrate formation temperature to higher values relative to the system without biosurfactant. Results from thermodynamic and kinetic studies suggest that rhamnolipids can be applied as environment friendly methane hydrate promoter.

Bioactivities and molecular networking-based elucidation of metabolites of potent actinobacterial strains isolated from the Unkeshwar geothermal springs in India - Mehetre, Gajanan T.; Vinodh, J. S.; Burkul, Bhushan B.; Desai, D.; Santhakumari, B.; Dharne, Mahesh S.; Dastager, Syed G (RSC Advances, 2019)
The bioactive potential of Actinobacteria endemic to hot springs has rarely been investigated. This study highlights the cultivable diversity and bioactivities of Actinobacteria associated with the Unkeshwar hot springs, India. Potent strains were evaluated for their biosynthetic potentials and metabolite analysis was performed using effective dereplication molecular networking tools. A total of 86 actinobacterial strains were isolated and grouped into 21 distinct genera, based on 16S rRNA gene sequence analysis. These strains included rare members such as Micromonospora, Marmoricola, Actinomadura, Cellulomonas, Cellulosimicrobium, Janibacter, Rothia, Barrentisimonas, Dietzia and Glycomyces. In antimicrobial screening, Micromonospora sp. strain GH99 and Streptomyces sp. strain GH176 were found to be potent antimicrobial strains. The metabolic extracts of these strains exhibited strong antimicrobial activity against Staphylococcus epidermidis (NCIM 2493), Shigella flexneri (NCIM 5265), Klebsiella pneumonia (NCIM 2098), and Salmonella abony (NCIM 2257). The extracts also displayed strong anti-biofilm and anticancer activities against Pseudomonas aeruginosa (NCIM 5029), Acinetobacter junii (NCIM 5188) and breast cancer cell line MCF7, respectively. Both strains also tested positive for the presence of the PKS biosynthetic gene cluster in their genomes. To effectively delineate the secondary metabolites, the extracts were subjected to MS/MS-guided molecular networking analysis. Structurally diverse compounds including the polyketides 22-dehydroxymethyl-kijanolide (GH99 strain) and Abyssomicin I (GH176 strain) were detected in the extracts. Interestingly, Brevianamide F was detected in the extract of Micromonospora, which has previously been mostly found in fungal species. Other compounds such as cyclic tripeptides, Cyclo(l-Pro-d-Ile) and Cyclo(d-Pro-l-Phe), were also identified in this strain. In summary, for the first time, we explored the diversity of Actinobacteria and evaluated their bioactive potential from the Unkeshwar hot springs. The potent strains isolated in the study could be useful in drug discovery programs.